2014
DOI: 10.1016/j.inteco.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of regional stock market integration in middle east: A conditional ICAPM approach

Abstract: Over recent years, several emerging market regions have actively taken part in globalisation movements and world market integration. However, the financial integration processes appear to vary over time, and differ considerably from one region to another. This paper investigates intraregional integration in the Middle East region during the period 1996-2008 using an international conditional Capital Asset Pricing Model (ICAPM) version that allows for dynamic changes in the degree of regional market integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The empirical analysis is conducted based on a nonlinear approach, which relies on the multivariate of GDC-GARACH. The study looks into market risk premium as the total risk of the economy used within financial integration (see, for example, Phylaktis and Ravazzolo 2002;Arouri 2006;Guesmi 2012).…”
Section: Financial Market Integration and Volatilitymentioning
confidence: 99%
“…The empirical analysis is conducted based on a nonlinear approach, which relies on the multivariate of GDC-GARACH. The study looks into market risk premium as the total risk of the economy used within financial integration (see, for example, Phylaktis and Ravazzolo 2002;Arouri 2006;Guesmi 2012).…”
Section: Financial Market Integration and Volatilitymentioning
confidence: 99%
“…They also deduced that the interdependence among MENA stock markets is growing but still weak. Guesmi and Teulon (2014) investigated the evolution of the process of integration in Middle East equity markets. Their estimated of the integration indices suggests that there are wide ranges in the degree of integration.…”
Section: Co-integration Estimation Techniques Developed Bymentioning
confidence: 99%
“…In addition to these determinants, GDP growth rate differential and time trend also has a significant relationship with the co-movement of stock market. Guesmi and Teulon (2014) examined the underlying forces of stock market integration of Middle East countries (Turkey, Israel, Jordan and Egypt). The results revealed that domestic (inflation, rate of spread variation and exchange rate volatility) and global (global interest rate, world market returns, and world market dividend yields) factors are significant in explaining the integration between the stock markets of Middle East countries.…”
Section: Empirical Evidences Of Determinants Of Stock Market Co-movementmentioning
confidence: 99%